2022
DOI: 10.1177/10422587221104820
|View full text |Cite
|
Sign up to set email alerts
|

Act or Wait-and-See? Adversity, Agility, and Entrepreneur Wellbeing across Countries during the COVID-19 Pandemic

Abstract: How can entrepreneurs protect their wellbeing during a crisis? Does engaging agility (namely, opportunity agility and planning agility) in response to adversity help entrepreneurs safeguard their wellbeing? Activated by adversity, agility may function as a specific resilience mechanism enabling positive adaption to crisis. We studied 3162 entrepreneurs from 20 countries during the COVID-19 pandemic and found that more severe national lockdowns enhanced firm-level adversity for entrepreneurs and diminished thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 135 publications
1
40
0
Order By: Relevance
“…In addition to the business-related pressures, entrepreneurs were also exposed to a high risk of burnout ( Torrès et al, 2022 ) and increased levels of stress ( Backman et al, 2021 ; Patel and Rietveld, 2020 ). The type and level of agility entrepreneurs adopt to respond to adversity affect their well-being in different ways ( Stephan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the business-related pressures, entrepreneurs were also exposed to a high risk of burnout ( Torrès et al, 2022 ) and increased levels of stress ( Backman et al, 2021 ; Patel and Rietveld, 2020 ). The type and level of agility entrepreneurs adopt to respond to adversity affect their well-being in different ways ( Stephan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Key lessons can be identified in corporate history, e.g., Ryanair's recession survival in 2008/2009 (Curran, 2010). The ability to recognize opportunities in times of crisis can be called opportunity agility (Stephan et al, 2022), and is based on four metrics, which are costs, time, robustness, and scope (Yauch, 2011).…”
Section: Third Er Principle: Turn Adversity Into Opportunitymentioning
confidence: 99%
“…The pandemic and the subsequent restrictions applied by governments have put businesses under severe strain across the world [ 4 ]. Because the self-employed are more vulnerable with limited in-house resources compared to large businesses, it can be assumed that they have been more negatively affected by the pandemic [ 5 , 6 ]. Studies during the first phase of the pandemic showed that European self-employed people reported a significantly worse household financial situation and higher job insecurity than organizational employees [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning health-related outcomes, studies have shown mixed and inconclusive results [ 6 ]. Many studies have shown that self-employed people are healthier, happier, and more satisfied with their job than employees [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%